1968
DOI: 10.1079/bjn19680023
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and stress

Abstract: I. When chicks were given a fat-free casein-gelatin diet and, after z weeks of age, 0.15 % silver acetate in the drinking water, they were found to have colourless exudates mainly in the pectoral region and partly in the peritoneal and pericardial spaces. Vitamin E and selenium, separately and together, failed to prevent this condition. Vitamin E was required together with methionine to prevent the condition. Methionine itself induced green staining of a few of the exudates.2. When lard was added to the casein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1969
1969
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The results of our studies are in agreement with those reported by Bunyan etal. (31,32) who found that unsaturated lipids do not become peroxidized after incorporation into the adipose tissue of vitamin E deficient rats. They also reject the in vivo antioxidant theory of vitamin E activity proposed by others (4,26,33-36) since the existence of peroxidation in vivo in the vitamin E deficient animal has not been substantiated (31,32).…”
Section: Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our studies are in agreement with those reported by Bunyan etal. (31,32) who found that unsaturated lipids do not become peroxidized after incorporation into the adipose tissue of vitamin E deficient rats. They also reject the in vivo antioxidant theory of vitamin E activity proposed by others (4,26,33-36) since the existence of peroxidation in vivo in the vitamin E deficient animal has not been substantiated (31,32).…”
Section: Generationmentioning
confidence: 99%
“…(31,32) who found that unsaturated lipids do not become peroxidized after incorporation into the adipose tissue of vitamin E deficient rats. They also reject the in vivo antioxidant theory of vitamin E activity proposed by others (4,26,33-36) since the existence of peroxidation in vivo in the vitamin E deficient animal has not been substantiated (31,32). In further support for our studies, Barber (37) has shown that the in vitro hemolysis test simply reveals the effective balance of pro-and antioxidant components in a system which is not related to conditions in vivo.…”
Section: Generationmentioning
confidence: 99%
“…Andrews et al (2) were unable to find evidence for the absorption of peroxides and therefore concluded that their toxic action took place on the intestinal wall. Other investigators also have concluded that intact peroxides are not absorbed (3)(4); still others (5)(6) have reported that feeding peroxides to rats leads to appreciable concentrations in the tissues. Nishida and Kummerow (7) obtained spectral evidence of diene conjugation in the lymph of rats dosed with methyl linoleate hydroperoxide and concluded therefore that some peroxide was absorbed.…”
Section: Introductionmentioning
confidence: 99%
“…Whether fatty acid peroxides are formed in animal tissues in vivo has been a controversial question for some years (1)(2)(3)(4)(5)(6). Substances which presumably are derived from peroxides or their degradation products have been detected in tissue extracts (7)(8)(9)(10), but it is difficult to prove their existence in the live organism.…”
Section: Introductionmentioning
confidence: 99%